2012
DOI: 10.3389/fmicb.2012.00188
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Amines in Raw and Processed Seafood

Abstract: The presence of biogenic amines (BAs) in raw and processed seafood, associated with either time/temperature conditions or food technologies is discussed in the present paper from a safety and prevention point of view. In particular, storage temperature, handling practices, presence of microbial populations with decarboxylase activity and availability of free amino acids are considered the most important factors affecting the production of BAs in raw seafood. On the other hand, some food technological treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
126
0
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(140 citation statements)
references
References 98 publications
5
126
0
9
Order By: Relevance
“…During October and November, increased content of this mycotoxin was established in samples of raw milk from farms. These results are consistent with some previous studies conducted by other researchers who reported an increase in concentration during autumn and winter months (Panariti, 2001;Visciano et al, 2015). However, samples from the individual producers in significant number of samples had concentrations of aflatoxin above EU regulation (EU, 2006) and even above Serbian regulation (Serbian Regulation, 2015).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…During October and November, increased content of this mycotoxin was established in samples of raw milk from farms. These results are consistent with some previous studies conducted by other researchers who reported an increase in concentration during autumn and winter months (Panariti, 2001;Visciano et al, 2015). However, samples from the individual producers in significant number of samples had concentrations of aflatoxin above EU regulation (EU, 2006) and even above Serbian regulation (Serbian Regulation, 2015).…”
Section: Resultssupporting
confidence: 83%
“…In some countries of the European Union, the dairy established internal system for a preventive or corrective action because of their consumers' protection or due to problems related with the increased level of aflatoxin M 1 in the past. In an Italian dairy, when value of aflatoxin M 1 in milk from suppliers exceeds 10 ng/kg the dairy reacts on preventive level and contacts the supplier, while in the situation when aflatoxin M 1 exceeds 20 ng/kg the supplier is suspended until concentration in milk is not returned to internal permitted level (Visciano et al, 2015). Swedish Dairy Association established the action limit for aflatoxin The aim of the present study is to investigate the occurrence of the aflatoxin M 1 in milk in the region of Autonomous Province of Vojvodina, the Republic of Serbia.…”
Section: Introductionmentioning
confidence: 99%
“…Yüksek düzeyde histamin içeren bir balık taze gibi görünebilmektedir. Bu nedenle besin güvenliğini sağlamada balıkçılar, işletmeciler, dağıtıcı firmalara ve marketlere büyük görev düşmektedir (Visciano, Schirone, Tofalo, & Suzzi, 2012 (Bosch et al, 2016).…”
Section: Balık Tüketimi Yarar and Risk Analiziunclassified
“…Kebusukan ikan yang disebabkan oleh aktivitas mikroba dan enzim di dalam tubuh ikan menghasilkan senyawa biogenik amin, yang terbentuk dari proses dekarboksilase asam amino bebas. Senyawa-senyawa biogenik amin tersebut antara lain histamin, kadaverin, putresin, tiramin, triptamin, spermin dan spermidin yang berasal dari asam amino bebas berupa histidin, ornitin, lisin, tirosin, triptofan dan arginin (Visciano et al 2012).…”
Section: Pendahuluanunclassified